Synthesis and properties of polypropylene/layered double hydroxide nanocomposites with different LDHs particle sizes - Qiu, L; Gao, Y; Lu, P; O'Hare, D; Wang, Q (Wiley, 2018)
In order to investigate whether the particle sizes of inorganic additives in polymer have an influence on the flame-retardant and other properties of the polymer, five types of Mg3Al–CO3layered double hydroxide (LDHs) with particle diameters of 80–100, 200–350, 500–550, 550–600, and 700–900 nm were synthesized using a hydrothermal method. The obtained Mg3Al–CO3LDHs were treated using the aqueous miscible organic solvent treatment method to give highly dispersed platelets in Polypropylene (PP). The thermal stability, flame retardancy, and mechanical properties of the PP/AMO–LDH nanocomposites were investigated systematically. The results showed that the thermal stability and flame retardancy of PP could be improved after incorporating AMO–LDHs. The temperature at 50% weight loss (T0.5) of PP/LDH (700–900 nm) nanocomposites with a LDH loading of 15 wt % was increased by 57 °C. When the LDHs loading was 40 wt %, the peak heat release rate (PHRR) of the PP/LDH nanocomposites with small LDHs particle sizes (<350 nm) was decreased by ca. 58%. The limiting oxygen index was increased by 5% for PP/LDH (80–100 nm) nanocomposites. The response surface regression results also indicated that both LDH particle size and loading have influence on PHRR, heat release capacity, tensile strength, and elongation at break. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46204.